Development of Persulukan Tarekat Naqsyabandiyah Jabal Qubis Foundation, Batang Kuis Deli Serdang - Afrida Nasution, Iis; Harahap , Indra; Wiji Utomo, Wahyu (Yayasan Salam Cerdas Al-Fattah, 2024)
Development of the Naqsyabandiyah Tarekat Jabal Qubis Foundation, Tanjung Morawa District, Deli Serdang Regency. The phenomenon of the development of the Tarekat Naqsyabandiyah has a tendency to have a positive impact on the younger and elderly generation. Psychologically good, which can have an effect on the social life of his followers. The aim of this research is to provide a general overview of the many motives driving the behavior of the general public and understand their relevance as a tribal society. The results of this research found that what motivates people to join the Naqsyabandiyah Jabal Qubis Tarekat is 1) because they want to be aware of the disadvantages of the world, because the word says that worldly life is nothing but the pleasure of deceiving. 2) because they want to carry out da'wah, namely being ascetic, says Allah subhana wata'ala. Follow people who do not ask you in return and they are the ones who are guided. 3) those who seek peace of mind and a happy life. 4) those who receive guidance from Allah SWT to repent and purify their hearts from bad behavior. The fact is that the Development of the Naqsyabandiyah Congregation, the Jabal Qubis Foundation was formed to make the people of Tanjung Morawa dedicated to worship.